Analisis Framing Pemberitaan Pasca Bencana Banjir Sumatra dalam Media Kompas.Com: Analisis Framing Model Robert M. Entman pada Artikel Media Kompas.Com - Rafii Fadilah Rahmman; Ana Fitriana Poerana; Nurkinan Nurkinan (IAI Nasional Laa Roiba Bogor, 2026)
This research is motivated by the high intensity of hydrometeorological disasters in Indonesia, specifically the devastating flash floods and landslides that struck three provinces in Sumatra in November 2025. During this crisis phase, mass media plays a crucial role in constructing social reality and influencing public perception regarding the post-disaster management process. This study aims to determine and analyze how the digital news portal Kompas.com framed information related to the crisis recovery progress through an article titled